Ethical and Legal Analysis of Child Disease Epidemiology Due to Environmental Exposure: A Systematic Literature Review - Nur, Nur Hamdani; Milda; Sitti Arifah; Yeni Paramata; Indar (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: Children are the most vulnerable group affected by environmental exposure, such as air pollution, contaminated water, chemicals, and heavy metals. This exposure increases the risk of respiratory, neurological disorders, and developmental delays, with both short-term and long-term impacts extending into adulthood. Recent studies have shown a high prevalence of diseases related to these exposures, such as asthma, neurological developmental delays, and cancer at young ages, emphasizing the need for a deeper science-based approach. However, the ethical and legal aspects of preventing and controlling environmental exposure remain insufficiently discussed in the scientific literature. Methods: This study uses a systematic literature review approach to analyze the relationship between environmental exposure and child disease epidemiology, focusing on ethical and legal dimensions. Relevant journal articles from 2015 to 2024 were reviewed through various databases using specific keywords and Boolean operators. Inclusion criteria included studies discussing child disease epidemiology and ethical or legal analyses related to environmental exposure. Results: The analysis indicates that ethical frameworks and legal regulations are crucial in ensuring the protection of children from environmental exposure risks. Developed countries have stricter regulations but often face challenges in implementation. In contrast, developing countries need more integrated policies informed by epidemiological research. A global approach and international collaboration are crucial to addressing the cross-border impacts of environmental contamination.